Bird migration and energetics simulations incorporating oil spill effects - Benjamin M. West; Mark L. Wildhaber; Wayne E. Thogmartin; Michael J. Hooper (Ecological Modelling, 2026)

Deformation, strains and velocities for the Alpine Himalayan Belt from trans-continental Sentinel-1 InSAR & GNSS - J.R. Elliott; J. Fang; M. Lazecký; Y. Maghsoudi; Q. Ou; J.A. Payne; C. Rollins; D. Wang; A. Hooper; T.J. Wright (Remote Sensing of Environment, 2026)

Barcoding‐Inferred Biodiversity of Shallow‐Water Indo‐Pacific Demosponges - Dirk Erpenbeck; Adrian Galitz; Michael L. Berumen; Gabriele Büttner; Cécile Debitus; Moritz Dirnberger; Merrick Ekins; Kathryn Hall; Leonard Namuth; Sylvain Petek; Neda Rahnamae; Maggie M. Reddy; et al. (Journal of Biogeography, 2026)
Aim The Indo‐Pacific is the world's largest marine biogeographic region. It is characterised by different degrees of connectivity among its subregions and harbours the majority of demosponge species currently known to science. Comparisons between regional sponge faunas have been undertaken in the past, mostly based on morphological species identification. The Sponge Barcoding Project, in tandem with regional DNA taxonomy campaigns, provides one of the largest DNA‐based taxonomic data collections from sponges of the Indo‐Pacific. Here, we utilise the barcoding data in the most extensive molecular biodiversity study of sponges to date, which reveals patterns of shallow‐water demosponge faunal connectivity, endemism and distribution in the Indo‐Pacific with a level of resolution unavailable in prior morphology‐based studies. Location Demosponge specimens in this study cover 13 marine provinces (MPs) of the Indo‐Pacific. Methods We classified demosponge barcodes from 1910 sponge samples into 701 molecular operational taxonomic units (MOTUs) using 28S rRNA. MOTU composition of the MPs was compared based on Jaccard and Sørenson dissimilarities and other biodiversity indices. Results Our data corroborated high endemism in MPs (up to 84.1% endemic MOTUs). Faunal overlaps are between the Red Sea and the Gulf, which displayed small connectivity with other MPs in the Western Indian Ocean. The Western Indian Ocean is a strong faunistic boundary to the Central Indo‐Pacific, to which the Polynesian sponge faunas were comparatively isolated as well. Main Conclusions Our data corroborate case studies on sponges that generally reject the presence of cosmopolitan or otherwise widespread sponge species, instead revealing high levels of regional endemism. This is consistent with similar observations and hypotheses in other marine invertebrates, and highlights the need for close regional monitoring to identify biodiversity changes. Connectivity among Indo‐Pacific MPs differs for demosponges in many aspects from that of other marine taxa, hypothetically due to their shorter pelagic larval phase.

Morrittospora corbiculae n. gen. n. sp., a microsporidian parasite infecting the invasive Asian clam Corbicula fluminea from the River Thames, London - Rachel Foster; Kelly S. Bateman; Paul F. Clark; Matthew J. Green; Chantelle Hooper; Stuart H. Ross; Paul Stebbing; Georgia M. Ward; David Bass (Journal of Invertebrate Pathology, 2026)

Overcoming barriers to build partnerships for managing plant invasions under global change - Jennifer L. Bufford; Angela J. Brandt; Kwek Yan Chong; Anna Hooper; Katie L. Kamelamela; Christy Martin; Ingrid M. Parker; Aníbal Pauchard; Katharine N. Suding; Duane A. Peltzer (Conservation Biology, 2026)
Non‐native plant invasions are a cross‐boundary conservation challenge, requiring coordinated management and policy responses underpinned by science. Global change is expected to exacerbate this challenge by changing abiotic and biotic drivers of invasive plant distribution, abundance, and impact. Current approaches may no longer be effective, and management must adapt to new threats and conditions. Collaborative personal and institutional partnerships are crucial to link research to practice and policy in order to better manage the complex drivers of invasions and mitigate their impacts under ongoing global change. We used examples from local to global scales to demonstrate how reciprocal knowledge exchange and project codesign among researchers, practitioners, and policy makers can improve conservation outcomes and benefits from invasive species management. Researchers provide expertise needed to apply concepts to new contexts, practitioners hold essential local knowledge, and policy makers balance competing priorities. Combining these strengths leads to more effective and resilient management of plant invasions. This highlights the central importance of collaboration among people, including Indigenous peoples and other local communities, in decision‐making and management. Best practices for developing partnerships between individual researchers and local and Indigenous communities, practitioners, and policy makers include engaging respectfully across knowledge and value systems, testing assumptions with data, considering ecological significance, and connecting across spatial scales. Structural solutions to overcome institutional and implementation barriers and develop effective partnerships include funding knowledge brokers and liaisons, collaboratively reviewing policies and practices, incentivizing long‐term relationships and goals, and codeveloping data collection and storage. The resulting intentional, long‐term partnerships will enable direct application of ecological knowledge to plant invasions and their management, support sustainable and locally backed solutions, and overcome lags in applying science to practice.

Increases in regional brain volume across two native South American male populations - Nikhil N. Chaudhari; Phoebe E. Imms; Nahian F. Chowdhury; Margaret Gatz; Benjamin C. Trumble; Wendy J. Mack; E. Meng Law; M. Linda Sutherland; James D. Sutherland; Christopher J. Rowan; L. Samuel Wann; Adel H. Allam; et al. (GeroScience, 2024)
Industrialized environments, despite benefits such as higher levels of formal education and lower rates of infections, can also have pernicious impacts upon brain atrophy. Partly for this reason, comparing age-related brain volume trajectories between industrialized and non-industrialized populations can help to suggest lifestyle correlates of brain health. The Tsimane, indigenous to the Bolivian Amazon, derive their subsistence from foraging and horticulture and are physically active. The Moseten, a mixed-ethnicity farming population, are physically active but less than the Tsimane. Within both populations ( N = 1024; age range = 46–83), we calculated regional brain volumes from computed tomography and compared their cross-sectional trends with age to those of UK Biobank (UKBB) participants ( N = 19,973; same age range). Surprisingly among Tsimane and Moseten (T/M) males, some parietal and occipital structures mediating visuospatial abilities exhibit small but significant increases in regional volume with age. UKBB males exhibit a steeper negative trend of regional volume with age in frontal and temporal structures compared to T/M males. However, T/M females exhibit significantly steeper rates of brain volume decrease with age compared to UKBB females, particularly for some cerebro-cortical structures (e.g., left subparietal cortex). Across the three populations, observed trends exhibit no interhemispheric asymmetry. In conclusion, the age-related rate of regional brain volume change may differ by lifestyle and sex. The lack of brain volume reduction with age is not known to exist in other human population, highlighting the putative role of lifestyle in constraining regional brain atrophy and promoting elements of non-industrialized lifestyle like higher physical activity.

Current extent and future opportunities for living shorelines in Australia - Rebecca L. Morris; Erin Campbell-Hooper; Elissa Waters; Melanie J. Bishop; Catherine E. Lovelock; Ryan J. Lowe; Elisabeth M.A. Strain; Paul Boon; Anthony Boxshall; Nicola K. Browne; James T. Carley; Benedikt J. Fest; et al. (Science of The Total Environment, 2024)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Stress during first gestation of ewes impairs memory and learning of male offspring - F. L. Henrique; A. J. Zanella; H. V. A. Bezerra; H. Z. Polato; A. C. Fernandes; H. B. Hooper; L. F. Pulido-Rodríguez; E. A. L. Titto; A. M. F. Pereira; C. G. Titto (Veterinary Research Communications, 2021)

Runs of homozygosity in killer whale genomes provide a global record of demographic histories - Andrew D. Foote; Rebecca Hooper; Alana Alexander; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; Tim Collins; Rochelle Constantine; Luciano Dalla Rosa; Nicholas J. Davison; et al. (Molecular Ecology, 2021)
Runs of homozygosity (ROH) occur when offspring inherit haplotypes that are identical by descent from each parent. Length distributions of ROH are informative about population history; specifically, the probability of inbreeding mediated by mating system and/or population demography. Here, we investigated whether variation in killer whale ( Orcinus orca ) demographic history is reflected in genome‐wide heterozygosity and ROH length distributions, using a global data set of 26 genomes representative of geographic and ecotypic variation in this species, and two F1 admixed individuals with Pacific‐Atlantic parentage. We first reconstructed demographic history for each population as changes in effective population size through time using the pairwise sequential Markovian coalescent (PSMC) method. We found a subset of populations declined in effective population size during the Late Pleistocene, while others had more stable demography. Genomes inferred to have undergone ancestral declines in effective population size, were autozygous at hundreds of short ROH ( 1.5 Mb) were found in low latitude populations, and populations of known conservation concern. These include a Scottish killer whale, for which 37.8% of the autosomes were comprised of ROH >1.5 Mb in length. The fate of this population, in which only two adult males have been sighted in the past five years, and zero fecundity over the last two decades, may be inextricably linked to its demographic history and consequential inbreeding depression.

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

Plasma metals as potential biomarkers in dementia: a case–control study in patients with sporadic Alzheimer’s disease - Jingshu Xu; Stephanie J. Church; Stefano Patassini; Paul Begley; Katherine A. B. Kellett; Emma R. L. C. Vardy; Richard D. Unwin; Nigel M. Hooper; Garth J. S. Cooper (BioMetals, 2018)

Understanding and managing fish populations: keeping the toolbox fit for purpose - J. R. Paris; K. D. Sherman; E. Bell; C. Boulenger; C. Delord; M. B. M. El‐Mahdi; E. A. Fairfield; A. M. Griffiths; C. Gutmann Roberts; R. D. Hedger; L. E. Holman; L. H. Hooper; et al. (Journal of Fish Biology, 2018)
Wild fish populations are currently experiencing unprecedented pressures, which are projected to intensify in the coming decades. Developing a thorough understanding of the influences of both biotic and abiotic factors on fish populations is a salient issue in contemporary fish conservation and management. During the 50th Anniversary Symposium of The Fisheries Society of the British Isles at the University of Exeter, UK, in July 2017, scientists from diverse research backgrounds gathered to discuss key topics under the broad umbrella of ‘Understanding Fish Populations’. Below, the output of one such discussion group is detailed, focusing on tools used to investigate natural fish populations. Five main groups of approaches were identified: tagging and telemetry; molecular tools; survey tools; statistical and modelling tools; tissue analyses. The appraisal covered current challenges and potential solutions for each of these topics. In addition, three key themes were identified as applicable across all tool‐based applications. These included data management, public engagement, and fisheries policy and governance. The continued innovation of tools and capacity to integrate interdisciplinary approaches into the future assessment and management of fish populations is highlighted as an important focus for the next 50 years of fisheries research.

Diversity of two widespread Indo-Pacific demosponge species revisited - Dirk Erpenbeck; Ratih Aryasari; Sarah Benning; Cécile Debitus; Emilie Kaltenbacher; Ali M. Al-Aidaroos; Peter Schupp; Kathryn Hall; John N. A. Hooper; Oliver Voigt; Nicole J. de Voogd; Gert Wörheide (Marine Biodiversity, 2017)

Systemic Inflammation during the First Postnatal Month and the Risk of Attention Deficit Hyperactivity Disorder Characteristics among 10 year-old Children Born Extremely Preterm - Elizabeth N. Allred; Olaf Dammann; Raina N. Fichorova; Stephen R Hooper; Scott J Hunter; Robert M. Joseph; Karl Kuban; Alan Leviton; Thomas Michael O’Shea; Megan N. Scott (Journal of Neuroimmune Pharmacology, 2017)

The presence of symptoms of testosterone deficiency in the exercise-hypogonadal male condition and the role of nutrition - David R. Hooper; William J. Kraemer; Catherine Saenz; Kevin E. Schill; Brian C. Focht; Jeff S. Volek; Carl M. Maresh (European Journal of Applied Physiology, 2017)

Quiet eye facilitates sensorimotor preprograming and online control of precision aiming in golf putting - Joe Causer; Spencer J. Hayes; James M. Hooper; Simon J. Bennett (Cognitive Processing, 2017)

Short Wave Amplification and Extreme Runup by the 2011 Tohoku Tsunami - Takenori Shimozono; Haiyang Cui; Julie D. Pietrzak; Hermann M. Fritz; Akio Okayasu; Andrew J. Hooper (Pure and Applied Geophysics, 2014)

Influence of training on markers of platelet activation in response to a bout of heavy resistance exercise - Brent C. Creighton; Brian R. Kupchak; Juan C. Aristizabal; Shawn D. Flanagan; Courtenay Dunn-Lewis; Brittanie M. Volk; Brett A. Comstock; Jeff S. Volek; David R. Hooper; Tunde K. Szivak; Carl M. Maresh; William J. Kraemer (European Journal of Applied Physiology, 2013)

Sex differences in creatine kinase after acute heavy resistance exercise on circulating granulocyte estradiol receptors - Megan R. Wolf; Maren S. Fragala; Jeff S. Volek; Craig R. Denegar; Jeffrey M. Anderson; Brett A. Comstock; Courtenay Dunn-Lewis; David R. Hooper; Tunde K. Szivak; Hui-Ying Luk; Carl M. Maresh; Keijo Häkkinen; et al. (European Journal of Applied Physiology, 2012)

Sinks for nitrogen inputs in terrestrial ecosystems: a meta‐analysis of 15 N tracer field studies - P. H. Templer; M. C. Mack; F. S. Chapin III; L. M. Christenson; J. E. Compton; H. D. Crook; W. S. Currie; C. J. Curtis; D. B. Dail; C. M. D'Antonio; B. A. Emmett; H. E. Epstein; et al. (Ecology, 2012)
Effects of anthropogenic nitrogen (N) deposition and the ability of terrestrial ecosystems to store carbon (C) depend in part on the amount of N retained in the system and its partitioning among plant and soil pools. We conducted a meta‐analysis of studies at 48 sites across four continents that used enriched 15 N isotope tracers in order to synthesize information about total ecosystem N retention (i.e., total ecosystem 15 N recovery in plant and soil pools) across natural systems and N partitioning among ecosystem pools. The greatest recoveries of ecosystem 15 N tracer occurred in shrublands (mean, 89.5%) and wetlands (84.8%) followed by forests (74.9%) and grasslands (51.8%). In the short term ( 15 N tracer application), total ecosystem 15 N recovery was negatively correlated with fine‐root and soil 15 N natural abundance, and organic soil C and N concentration but was positively correlated with mean annual temperature and mineral soil C:N. In the longer term (3–18 months after 15 N tracer application), total ecosystem 15 N retention was negatively correlated with foliar natural‐abundance 15 N but was positively correlated with mineral soil C and N concentration and C : N, showing that plant and soil natural‐abundance 15 N and soil C:N are good indicators of total ecosystem N retention. Foliar N concentration was not significantly related to ecosystem 15 N tracer recovery, suggesting that plant N status is not a good predictor of total ecosystem N retention. Because the largest ecosystem sinks for 15 N tracer were below ground in forests, shrublands, and grasslands, we conclude that growth enhancement and potential for increased C storage in aboveground biomass from atmospheric N deposition is likely to be modest in these ecosystems. Total ecosystem 15 N recovery decreased with N fertilization, with an apparent threshold fertilization rate of 46 kg N·ha −1 ·yr −1 above which most ecosystems showed net losses of applied 15 N tracer in response to N fertilizer addition.

Sex Pheromone Communication in Two Sympatric Neotropical Stink Bug Species Chinavia ubica and Chinavia impicticornis - M. C. Blassioli-Moraes; R. A. Laumann; M. W. M. Oliveira; C. M. Woodcock; P. Mayon; A. Hooper; J. A. Pickett; M. A. Birkett; M. Borges (Journal of Chemical Ecology, 2012)

Validation of a high-throughput microtissue fabrication process for 3D assembly of tissue engineered cartilage constructs - B. S. Schon; K. Schrobback; M. van der Ven; S. Stroebel; G. J. Hooper; T. B. F. Woodfield (Cell and Tissue Research, 2012)

Diversity and distribution of the bioactive actinobacterial genus Salinispora from sponges along the Great Barrier Reef - M. E. Vidgen; J. N. A. Hooper; J. A. Fuerst (Antonie van Leeuwenhoek, 2012)

Effects of human disturbance on the diet composition of wild red deer (Cervus elaphus) - Sevvandi Jayakody; Angela M. Sibbald; Robert W. Mayes; Russell J. Hooper; Iain J. Gordon; Xavier Lambin (European Journal of Wildlife Research, 2011)

Soil lead (Pb) in residential transects through Lubbock, Texas: a preliminary assessment - Ray W. Brown; Chris Gonzales; Michael J. Hooper; Andrew C. Bayat; Ashley M. Fornerette; Tobias J. McBride; Thomas Longoria; Howard W. Mielke (Environmental Geochemistry and Health, 2008)

Will increased storm disturbance affect the biodiversity of intertidal, nonscleractinian sessile fauna on coral reefs? - S. J. WALKER; B. M. DEGNAN; J. N. A. HOOPER; G. A. SKILLETER (Global Change Biology, 2008)
Relatively little is known about how the future effects of climatic change, including increases in sea level, temperature and storm severity and frequency, will impact on patterns of biodiversity on coral reefs, with the notable exception of recent work on corals and fish in tropical reef ecosystems. Sessile invertebrates such as ascidians, sponges and bryozoans occupying intertidal rubble habitats on coral reefs contribute significantly to the overall biodiversity and ecosystem function, but there is little or no information available on the likely impacts on these species from climate change. The existing strong physical gradients in these intertidal habitats will be exacerbated under predicted climatic change. By examining the distribution and abundance of nonscleractinian, sessile invertebrate assemblages exposed to different levels of wave action and at different heights on the shore around a coral reef, we show that coral reef intertidal biodiversity is particularly sensitive to physical disturbance. As physical disturbance regimes increase due to more intense storms and wave action associated with global warming, we can expect to see a corresponding decrease in the diversity of these cryptic sessile assemblages. This could impact negatively on the future health and productivity of coral reef ecosystems, given the ecosystem services these organisms provide.

Environmental detection of octahaem cytochrome c hydroxylamine/hydrazine oxidoreductase genes of aerobic and anaerobic ammonium‐oxidizing bacteria - Markus C. Schmid; Alan B. Hooper; Martin G. Klotz; Dagmar Woebken; Phyllis Lam; Marcel M. M. Kuypers; Andreas Pommerening‐Roeser; Huub J. M. Op Den Camp; Mike S. M. Jetten (Environmental Microbiology, 2008)
Summary Bacterial aerobic ammonium oxidation and anaerobic ammonium oxidation (anammox) are important processes in the global nitrogen cycle. Key enzymes in both processes are the octahaem cytochrome c (OCC) proteins, hydroxylamine oxidoreductase (HAO) of aerobic ammonium‐oxidizing bacteria (AOB), which catalyses the oxidation of hydroxylamine to nitrite, and hydrazine oxidoreductase (HZO) of anammox bacteria, which converts hydrazine to N 2 . While the genomes of AOB encode up to three nearly identical copies of hao operons, genome analysis of Candidatus ‘Kuenenia stuttgartiensis’ showed eight highly divergent octahaem protein coding regions as possible candidates for the HZO. Based on their phylogenetic relationship and biochemical characteristics, the sequences of these eight gene products grouped in three clusters. Degenerate primers were designed on the basis of available gene sequences with the aim to detect hao and hzo genes in various ecosystems. The hao primer pairs amplified gene fragments from 738 to 1172 bp and the hzo primer pairs amplified gene fragments from 289 to 876 bp in length, when tested on genomic DNA isolated from a variety of AOB and anammox bacteria. A selection of these primer pairs was also used successfully to amplify and analyse the hao and hzo genes in community DNA isolated from different ecosystems harbouring both AOB and anammox bacteria. We propose that OCC protein‐encoding genes are suitable targets for molecular ecological studies on both aerobic and anaerobic ammonium‐oxidizing bacteria.

Evolution of an octahaem cytochrome c protein family that is key to aerobic and anaerobic ammonia oxidation by bacteria - Martin G. Klotz; Markus C. Schmid; Marc Strous; Huub J. M. Op Den Camp; Mike S. M. Jetten; Alan B. Hooper (Environmental Microbiology, 2008)
Summary The biogeochemical nitrogen cycle is mediated by many groups of microorganisms that harbour octahaem cytochromes c (OCC). In this study molecular evolutionary analyses and the conservation of predicted functional residues and secondary structure were employed to investigate the descent of OCC proteins related to hydroxylamine oxidoreductase (HAO) and hydrazine oxidoreductase (HZO) from pentahaem cytochrome c nitrite reductase (NrfA). An o ctahaem cytochrome c n itrite r eductase (ONR) was shown to be a possible intermediate in the process. Analysis of genomic neighbourhoods of OCC protein‐encoding genes revealed adjacent conserved genes whose products, together with HAO, provide a path of electron transfer to quinone and constitute a functional catabolic module. The latter has evolved more than once under a variety of functional pressures on the catabolic lifestyles of their bacterial hosts. Structurally, the archetypical long helices in the large C‐terminal domain of the proteins as well as the distal axial ligands to most haems were highly conserved in NrfA and all descendents. Residues known to be involved in the nitrite reductase activity of NrfA including the ‘CxxCK’ motif at the catalytic haem, the substrate and Ca binding sites, and the nitrite and ammonium channels were conserved in the eight representatives of ONR. In the latter, a unique cysteine has been inserted above the active site. The 64 other OCC proteins differed from ONR by the absence of the ‘CxxCK’ motif, the channel residues and most of the Ca‐binding residues and the conserved presence of an ‘Asp–His’ pair inserted above the active site as well as the tyrosine that forms an intersubunit cross‐link to the catalytic haem of HAO. Our proposed scenario of evolution of OCC proteins in the HAO family from NrfA is supported by (i) homology based on sequence and structure, (ii) its wide distribution among bacterial taxa, (iii) the dedicated interaction with specific proteins, and it is (iv) congruent with geological history.

Effects on kidney disease, fertility and development in mice inheriting a protein-truncating Denys-Drash syndrome allele (Wt1 tmT396) - Charles E. Patek; David G. Brownstein; Stewart Fleming; Caroline Wroe; Lorraine Rose; Anna Webb; Rachel L. Berry; Paul S. Devenney; Marion Walker; Oliver D. K. Maddocks; Nicola J. Lawrence; David J. Harrison; et al. (Transgenic Research, 2008)

Arsenic, Cadmium, Copper, Lead, and Selenium in Migrating Blue-Winged Teal (Anas discors L.) - A. M. Fedynich; B. M. Ballard; T. J. McBride; J. A. Estrella; J. M. Garvon; M. J. Hooper (Archives of Environmental Contamination and Toxicology, 2007)

Mercury and Methylmercury Accumulation and Excretion in Prairie Voles (Microtus ochrogaster) Receiving Chronic Doses of Methylmercury - G. P. Cobb; A. W. Moore; K. T. Rummel; B. M. Adair; S. T. McMurry; M. J. Hooper (Archives of Environmental Contamination and Toxicology, 2007)

Analysing the effect of candidate genes on complex traits: an application in multiple sclerosis - Tineke Hooper-van Veen; Johannes Berkhof; Chris H. Polman; Bernard M. J. Uitdehaag (Immunogenetics, 2006)

Control of Witchweed Striga hermonthica by Intercropping with Desmodium spp., and the Mechanism Defined as Allelopathic - Zeyaur R. Khan; Ahmed Hassanali; William Overholt; Tsanuo M. Khamis; Antony M. Hooper; John A. Pickett; Lester J. Wadhams; Christine M. Woodcock (Journal of Chemical Ecology, 2002)

Characterization of (1R,4S,4aR,7S,7aR)-Dihydronepetalactol as a Semiochemical for Lacewings, Including Chrysopa spp. and Peyerimhoffina gracilis - A. M. Hooper; B. Donato; C. M. Woodcock; J. H. Park; R. L. Paul; K. S. Boo; J. Hardie; J. A. Pickett (Journal of Chemical Ecology, 2002)

Ice Storm Damage and Early Recovery in an Old-Growth Forest - Stéphanie M. Duguay; Ken Arii; Michael Hooper; Martin J. Lechowicz (Environmental Monitoring and Assessment, 2001)

Velocity specificity in early training of the knee extensors after anterior cruciate ligament reconstruction - Matthew C. Morrissey; David M. Hooper; Wendy I. Dreschler; Helen J. Hill; Thomas Bucknill (European Journal of Applied Physiology, 2000)

Contaminant Exposure and Biomarker Responses in Spectacled Eiders ( Somateria fischeri ) from St. Lawrence Island, Alaska - K. A. Trust; K. T. Rummel; A. M. Scheuhammer; I. L. Brisbin Jr.; M. J. Hooper (Archives of Environmental Contamination and Toxicology, 2000)

Monitoring and Assessment of Swainson's Hawks in Argentina Following Restrictions on Monocrotophos Use, 1996–97 - Michael I. Goldstein; T. E. Lacher; M. E. Zaccagnini; M. L. Parker; M. J. Hooper (Ecotoxicology, 1999)

A Novel Approach for Isolation of Volatile Chemicals Released by Individual Leaves of a Plant in situ - Nicky G. Agelopoulos; Antony M. Hooper; Sangita P. Maniar; John A. Pickett; Lester J. Wadhams (Journal of Chemical Ecology, 1999)

Avian Exposure to Pesticides in Costa Rican Banana Plantations - S. R. Mortensen; K. A. Johnson; C. P. Weisskopf; M. J. Hooper; T. E. Lacher; R. J. Kendall (Bulletin of Environmental Contamination and Toxicology, 1998)

Spreading and Retention of Vaginal Formulations in Post-Menopausal Women as Assessed by Gamma Scintigraphy - J. Brown; G. Hooper; C. J. Kenyon; S. Haines; J. Burt; J. M. Humphries; S. P. Newman; S. S. Davis; R. A. Sparrow; I. R. Wilding (Pharmaceutical Research, 1997)

Enzymology of the oxidation of ammonia to nitrite by bacteria - Alan B. Hooper; Todd Vannelli; David J. Bergmann; David M. Arciero (Antonie van Leeuwenhoek, 1997)